SOME NATURAL FLAVONOIDS FROM GUAVA (PSIDIUM GUAJAVA L.) AGAINST SARS COV-2, INSILICO PREDICTION AND DRUGS EVALUATION - Arief Kusuma Wardani (Jurnal Farmasi Sains dan Praktis, 2022)
SARS-CoV-2 is a new virus that little is known about it, which has infected many people around the world. As COVID-19 cases continue to rise, it means more people are being infected, and there is still no targeted therapy for COVID-19 patients. Important for an emergency is to find the most potential Hesperidin, Kaempferol-3,4'-di-O-methyl ether (Ermanin); Myricetin-3-glucoside, Peonidine 3-(4’-arabinosylglucoside); Quercetin 3-(2G-rhamnosylrutinoside); and Rhamnetin 3-mannosyl-(1–2)-alloside as a lead compound from guava to develop new drugs from flavonoid analogue. Docking method through iGEMDOCK software was used to design a new lead compound candidate from several flavonoid and study its interaction with of 3CLpro (PDB ID: 7DPU). The docking method were carried out using the iGEMDOCK software version v2.1, also in the chimera-1.13.1 program is used to know the interaction profile. Druglike properties were calculated using Lipinski’s rule of five as calculated using SWISSADME prediction. Toxicity prediction herein used ADMETSAR webserver (http://lmmd.ecust.edu.cn:8000/predict/). Less toxic and showing greater affinity with a docking score stronger was found in Quercetin, is apart from good pharmacokinetic profile.